Levels of 25 Hydroxyvitamin D in Normotensive Pregnancy and Severe Preeclampsia - Palinoan, Meynita; Kaeng, Juneke J; Suparman, Erna (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To determine the ratio of 25-hydroxyvitamin D levels innormotensive pregnancy and severe preeclampsia.   Methods: This study was an analytic cross-sectional study witht-test. The subject of this study consists of 17 samples normotensivepregnancy and 17 samples severe preeclampsia. This study wasconducted and evaluated from August 2016 until December 2016 atDepartment of Obstetrics and Gynecology Faculty of MedicineUniversitas Sam Ratulangi Prof. Dr. R.D. Kandou Hospital Manadoand satellite hospital in Manado. Samples were taken from serumas much as 5 ccs and were analyzed using CLIA at Prodia clinicallaboratory. Data were analyzed with SPSS version 20.0.   Results: By using the t- test, there were significant differences in25-hydroxyvitamin D levels between normotensive pregnancygroup (24.771  6.9567ng/ml) and severe preeclamptic group(17.712  3.7513ng/ml), p = 0.001.   Conclusion: Levels of 25-hydroxyvitamin D in normotensive pregnancysignificantly higher compared to severe preeclampsia so it canbe concluded that the levels of 25-hydroxyvitamin D were associatedwith preeclampsia.   Keywords: 25-hydroxyvitamin D, normotensive, severe preeclampsia